Kualitas Pelayanan, Partisipasi Anggota dan Pengaruhnya terhadap SHU Koperasi Fungsional (Studi Kasus KPRI di Kabupaten Badung Provinsi Bali) - Dwi Kusumarini, Ni Made Winny; Tisnawati, Ni Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 5, No. 1, Januari 2016 (pp. 1 - 215), 2016)
The cooperative is one of the strengths of economic container in the Indonesia economy. The number of units in the district Badung KPRI lowest compared with other district/city in the province of Bali. Service quality and member participation is expected able to increase the amount of net income (SHU) obtained cooperatives. This study aims to determine the direct effect of service quality and participation of the members of net income (SHU) and the indirect influence between the quality of service to net income (SHU) through the participation of members. This study was conducted in seven Employees Cooperative Republic of Indonesia ( KPRI ) are active and carry out RAT 2014 in Badung . The data used in this study are primary data , by taking 98 samples using the method of proportional random purposive sampling while the analysis method used is the analysis of Confirmatory Factor Analysis and Path or path analysis to determine the influence of direct and Sobel test to determine the effect is not immediate. The analysis showed that the quality of services and significant positive direct effect on the participation of members. Quality of service and the direct participation of members of a positive and significant impact on operating results (SHU). Indirectly affect service quality significantly to net income (SHU) through the participation of members. Means the participation of members of an intervening variable of service quality and operating results (SHU).
Keywords: quality of service, the participation of members, net income (SHU)